A methods engineering study on Dynamic Manufacturing Corporation - Dizon, Charity; Limyu, Rey Jason; Moraga, Melissa (Diliman, Quezon City College of Engineering, 2004)
This paper is a methods engineering study on Dynamic Manufacturing Corporation. Dynamic Manufacturing Corporation is a manufacturing company that produces tapes, cords and straps. It has four sections namely braiding, loom, crochet and packaging. This paper discusses the problems encountered in the company and proposes recommendations and implementations that may help them improve productivity and worker efficiency. The study is conducted per section so as to ease the consecution. The operations in the said company are highly mechanized. Numerous machines are used in each section. Thus, noise, vibrations and humidity are conditions faced by the workers that can only be reduced and not eliminated. Opening most of the closed windows would be of great help. The workplace is also messy because of the nature of the work. Plus, boxes that serve as nests for finished products are on the floor and are near the greasy machine. Layout is another important problem to be considered. There are three buildings and so there are great distances between different areas. This is very evident in the storage and working area, which are located in separate buildings. Workers experience heavy loads. Although there are carts present, they manually carry materials like threads and beams from the storage to the work area. So it is a big help that carts be utilized. Because of the machine design, the workers encounter awkward positions during setting up, etc. Hence, seats and machine heights should be noted. The main problem arises from the absence of systematic procedure. This is very interesting for this is the foundation of the work. Also, there is an undetermined worker-machine ratio. As a course of action, the group conducted a time study and proposed a work standard and procedure. All of these will be discussed in detail in the next pages. Tables and forms will be provided for better understanding. Implementing the proposed recommendations is not costly. In the facility layout, few revisions are made, which may be finished in a day. This would not affect the productivity of the company when compared to the benefits it will provide. The recommendations in the worker sense are more of guidance and learning, the hardest part. Therefore, the only problem in the implementation is the worker resistance, which is innate to all workers.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Dynamic Manufacturing Corporation; Clothing trade -- Philippines; Textile industry -- Philippines; Systems analysis